A Fluorescent High-Throughput Assay for Double-Stranded DNA: the RediPlate PicoGreen Assay - Batchelor, R.; Hagen, D.; Johnson, I.; Beechem, J. (Combinatorial Chemistry & High Throughput Screening, 2003)
The fluorescent PicoGreen® reagent for detection and quantitation of double-stranded DNA has been adapted for high-throughput screening: the RediPlate PicoGreen double-stranded DNA assay format. In the RediPlate PicoGreen assay format, the PicoGreen reagent is predistributed and co-dried into either 96- or 384- well microplates with the excipient trehalose. The user resuspends the dried reagents upon adding DNA, and measures the resulting fluorescence after a five minute incubation. Replicate fluorescence measurements on nominally identical wells have less than a 5% coefficient of variation. The assay is linear from 5 to 500 ng / ml DNA in a 200 μl volume. The RediPlate PicoGreen assay format retains the advantages of the original PicoGreen reagent - sensitivity, speed, and specificity - but in a high-throughput format.
Keywords: microplate